Fabricación de envases comestibles a base de almidón y harina de cáscara de papa fortificada con pulpa de café - Arroyo Villanueva, José Armando (2023)
For the production of edible packaging made with agro-industrial residues such as potato peel and coffee pulp, the objective was to find the proportion of starch and flour in potato peel, as well as the coffee pulp with the best mechanical, physical and sensory. Potato peel starch and flour were extracted and characterized. With which, the containers were formulated. These had 2 presentations. One produced with flour (CO) and the other with chips (CHI) of coffee pulp. For each one, 9 treatments were elaborated, in addition to the treatment without pulp (CONTROL). In total, 19 treatments. ANOVA was used to support the results. The sensory test of taste, smell, color, texture and crispness was carried out using a hedonic test with a scale of 1 to 5. For the mechanical analysis, tension and compression tests were carried out by means of a texture analyzer. For the physical tests, the analysis of color, water absorption capacity, thickness and density were carried out. The production yield was between 66 and 100%. The best proportions were: 60 g of starch, 5 g of potato peel flour and 2.5 g of coffee pulp chips. Also, 50 g of starch, 15 g of potato peel flour and 7.5 g of coffee pulp flour. For these containers, the mechanical cutting and Volodkevich tests were carried out; FTIR analysis; health test; nutritional value and availability of iron. Giving as results that, the container with the presentation of coffee pulp flour had better characteristics. For example, a cutting work of 12.13±1.08 N/mm.sec, firmness of 12.79±1.54 N/mm. Being, a safe food 15 days after processing, with an assimilation of iron between 1.13 mg/kg to 1.81 mg/kg. It is recommended to evaluate the useful life of these containers, to be sure of when they are no longer suitable for human consumption. As well as, find the cost of elaboration and its realization with other agro-industrial residues.